Gambaran Pengelolaan Limbah Infeksius oleh Perawat di Ruang Rawat Inap RSUD Arifin Achmad Provinsi Riau - Dhea Putri Primadana Arum (Jurnal Medika Hutama, 2022)
Hospital activities produce various kinds of hospital wastes, and one of them is infectious waste. Poor infectious waste management leads to health and environment problems. This study aimed to provide description of infectious waste management by nurses stationed at class III inpatient room (Dahlia, Edelweis, Kenanga, Krisan) of Arifin Achmad General Hospital of Riau Province. It applied simple descriptive design involving 66 nurses selected using total sampling technique. The data was gathered using questionnaire, while the data analysis was done using univariate analysis. The results showed that 48 nurses (72.7%) conducted proper infectious waste management. In addition, 50 of the nurses surveyed (75.8%) possessed a good knowledge of infectious waste management. Common types of infectious waste found at inpatients rooms are mostly patient-contaminated from isolation wards, such as: medical gauzes, swab gauzes and other infectious waste. As many as 50 nurses (75.8%) conducted infectious waste segregation well, and 51 nurses (77.3%) conducted infectious waste packaging properly. In general, majority of nurses stationed at inpatient rooms conducted proper infectious waste management. It is expected that this study to make nurses improve the quality of infectious waste management at inpatient rooms for better in the future.